2013
DOI: 10.1111/scd.12056
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of people living with HIV/AIDS attending a specialized service in Brazil

Abstract: Poor oral health of the PLWHA was mainly influenced by sociodemographic factors and use and satisfaction with service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
19
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 31 publications
(43 reference statements)
10
19
3
Order By: Relevance
“…This study showed a correlation between the average age of cases and the mean value of the DMFT index, decayed, and missing teeth. Similar to this study, Soares et al showed that the DMFT index and missing teeth increase with patients’ age, but there was no relationship between age and decayed teeth (11). In contrast with this study, Santo et al observed no relationship between the DMFT index and age.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This study showed a correlation between the average age of cases and the mean value of the DMFT index, decayed, and missing teeth. Similar to this study, Soares et al showed that the DMFT index and missing teeth increase with patients’ age, but there was no relationship between age and decayed teeth (11). In contrast with this study, Santo et al observed no relationship between the DMFT index and age.…”
Section: Discussionsupporting
confidence: 85%
“…This noted difference may be traced to differences of race, oral hygiene behaviors, nutrition, types of treatment, the fluoride content of drinking water, extent of dental services, and the implementation of training and preventative programs. In this study, the mean of filled teeth was apparently lower than others (3, 9, 11-13). Since the people of the studied region need serious dental services, essential plans should be prepared to build a context from which these people can benefit by using dentistry services.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations